2021
DOI: 10.3390/diagnostics11061120
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Ductal Hyperplasia after Vacuum-Assisted Breast Biopsy: Can We Reduce the Upgrade to Breast Cancer to an Acceptable Rate?

Abstract: (1) Background: to evaluate which factors can reduce the upgrade rate of atypical ductal hyperplasia (ADH) to in situ or invasive carcinoma in patients who underwent vacuum-assisted breast biopsy (VABB) and subsequent surgical excision. (2) Methods: 2955 VABBs were reviewed; 141 patients with a diagnosis of ADH were selected for subsequent surgical excision. The association between patients’ characteristics and the upgrade rate to breast cancer was evaluated in both univariate and multivariate analyses. (3) Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
2
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 41 publications
0
12
2
3
Order By: Relevance
“…In our study, we propose a predictive model in order to minimize the risk of diagnostic underestimation in a smaller group of patients. Nomograms are predictive tools that allow, considering the multiples features, an assessment of the risk of underestimation [ 27 ]. With our nomogram, you are able to evaluate if a patient has a predicted probability of diagnostic underestimation below 2%.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we propose a predictive model in order to minimize the risk of diagnostic underestimation in a smaller group of patients. Nomograms are predictive tools that allow, considering the multiples features, an assessment of the risk of underestimation [ 27 ]. With our nomogram, you are able to evaluate if a patient has a predicted probability of diagnostic underestimation below 2%.…”
Section: Discussionmentioning
confidence: 99%
“…Als Grund wird angeführt, dass in der Regel an der Nadelbiopsie die endgültige Ausdehnung der atypischen intraduktalen Epithelproliferation nicht festgelegt werden kann und somit keine sichere Grenzziehung zwischen ADH und low-grade duktalem Carcinoma in situ (DCIS) möglich ist [ 4 , 16 , 47 , 55 ]. Zahlreiche Studien haben versucht morphologische Kriterien an den präoperativen Biopsien zu identifizieren, die voraussagen können, welche ADH-Fälle im nachfolgenden chirurgischen Präparat höhergradige Läsionen (wie DCIS, invasives Karzinom) oder andere B3-Läsionen wie klassische lobuläre Neoplasie (LN) oder flache epitheliale Atypie (FEA) enthalten [ 34 , 38 , 41 ]. Diese Kriterien (unter anderem die Assoziation zu Verkalkungen, die Zahl der betroffenen Gangstrukturen oder der Nachweis von assoziierten intraläsionalen Nekrosen) können zwar in Einzelfällen prädiktiv sein, eine signifikante Assoziation zwischen diesen Faktoren an der Stanzbiopsie und den Diagnosen im Operationspräparat konnte aber bisher nicht etabliert werden [ 34 , 38 , 41 ].…”
Section: Atypische Duktale Hyperplasieunclassified
“…Zahlreiche Studien haben versucht morphologische Kriterien an den präoperativen Biopsien zu identifizieren, die voraussagen können, welche ADH-Fälle im nachfolgenden chirurgischen Präparat höhergradige Läsionen (wie DCIS, invasives Karzinom) oder andere B3-Läsionen wie klassische lobuläre Neoplasie (LN) oder flache epitheliale Atypie (FEA) enthalten [ 34 , 38 , 41 ]. Diese Kriterien (unter anderem die Assoziation zu Verkalkungen, die Zahl der betroffenen Gangstrukturen oder der Nachweis von assoziierten intraläsionalen Nekrosen) können zwar in Einzelfällen prädiktiv sein, eine signifikante Assoziation zwischen diesen Faktoren an der Stanzbiopsie und den Diagnosen im Operationspräparat konnte aber bisher nicht etabliert werden [ 34 , 38 , 41 ]. Es gibt keine radiologischen Merkmale, die helfen, mit ADH assoziierte Verkalkungen von denen anderer Läsionen zu unterscheiden, wie z.…”
Section: Atypische Duktale Hyperplasieunclassified
See 1 more Smart Citation
“…Recent studies have demonstrated that VAB is a reliable and effective alternative to OE of B3 lesions without atypia, such as papillomas and radial scars (RSs) [6,[12][13][14][15][16][17]. This has led to an increasing use of VAB and subsequent observation in nonsurgically managed B3 lesions in some countries [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%